Association of Pulmonary Hypertension and the Stages of Chronic Kidney Disease: A Cross-Sectional Study - Akhtaruzzaman, Muhammed; Arafat, Mohammad Ali; Ahamed, Monir Uddin; Rahman, Rezwanur; Haq, Arman Ibne (Community Based Medical Journal, 2025)
Pulmonary hypertension (PH) has emerged as a significant cardiovascular complication in patients with chronic kidney disease (CKD), with studies suggesting a bidirectional relationship between renal dysfunction and pulmonary vascular changes. However, the exact association of pulmonary hypertension and different stages of CKD remains poorly characterized, particularly in South Asian population. A cross-sectional, observational study was conducted in Bangladesh Medical College Hospital, Dhaka, Bangladesh, from January to December of 2023, to assess the association between pulmonary hypertension and different stages of chronic kidney disease. A purposive sample of 120 CKD patients was enrolled and categorized based on KDIGO guidelines. Besides, PH was diagnosed using echocardiography with estimated pulmonary artery systolic pressure (ePASP) ≥25 mmHg. Then demographic, clinical, and laboratory data were collected and analyzed. Among 120 CKD patients, 46 were in pulmonary hypertension (PH) group and 74 were in non-PH group. PH group was significantly older than the non-PH group (58.2±10.4 vs. 51.8±12.6 years; p=0.003). However, no significant differences were observed in gender distribution, BMI, diabetes, or hypertension between two groups. A strong association was found between CKD stages and PH prevalence that progressively increased from Stage 3 (27.1%) to Stage 5 (54.8%) (p<0.001). Patients with prolonged CKD duration (>12 months) exhibited more moderate and severe PH (53.6% and 21.4% respectively). Patients in PH group had significantly higher systolic blood pressure (148±16 mmHg vs. 138±14 mmHg; p<0.05), more frequent oedema (69.6% vs. 37.8%; p<0.001), and worse renal function (eGFR 28.4±16.2 ml/min/1.73m² vs. 45.6±18.3 ml/min/1.73m²; p<0.001). Multivariate logistic regression identified advanced CKD stages (OR 3.12, 95% CI 1.89–5.15; p=0.001), haemoglobin <10 g/dL (OR 2.45, 95% CI 1.32–4.56; p=0.004), fluid overload (OR 2.12, 95% CI 1.24–3.62; p=0.006), and age >55 years (OR 1.89, 95% CI 1.15–3.10; p=0.012) as independent predictors of PH. Echocardiographic assessment revealed higher ePASP (42.3±8.1 mmHg vs. 21.6±5.4 mmHg; p<0.001), reduced TAPSE (1.8±0.3 cm vs. 2.2±0.4 cm; p<0.001), enlarged right ventricular diameter (3.6±0.5 cm vs. 2.8±0.4 cm; p<0.001), and elevated right atrial pressure (10.2±2.1 mmHg vs. 6.8±1.9 mmHg; p<0.05) in PH group. CBMJ 2025 July: vol. 14 no. 02 P:173-179